Functional Duality of SOEs: Comparative Legal Governance of Indonesia and Singapore's Temasek - Thimotius Melkysedekh Yuliawan (Legtimacy: Journal of Law and Islamic Law, 2026)
This article comprehensively examines the normative tension resulting from the functional duality of state enterprises in Indonesia, which remain perpetually trapped between corporate profit maximization and national public service obligations. The establishment of the investment superholding triggers a perilous juridical identity crisis that potentially escalates profound moral hazard risks. Employing a functional comparative legal methodology, this study dissects the governance asymmetry between Indonesia and Temasek Holdings in Singapore. Findings confirm that the domestic public finance legal regime systematically distorts the doctrinal operationalization of the business judgment rule, thereby engendering structural criminalization vulnerabilities over commercial risks. Therefore, this study radically urges legal reconstruction requiring the statutory redefinition of the superholding as a strictly private entity. This prescriptive resolution necessitates the strict codification of absolute safe harbor provisions to mitigate political intervention while simultaneously securing corporate autonomy. This step is essential to harmonize domestic investment governance with global OECD competitive neutrality standards.